Captured by grace : no one is beyond the reach of a loving God - Jeremiah, David, 1941- (Nashville, Tenn. : Integrity Publishers, 2006)
Presents the personal stories of Saint Paul and John Newton, composer of the hymn "Amazing Grace," to illustrate the workings of grace, discussing how its power can be used to overcome difficulties and increase love and tolerance for others.
Prelude: The hunters and the hunted -- Part One: Grace for the past : The captivating presence of grace -- Amazing grace, how sweet the sound ; The compassionate plan of grace -- That saved a wretch like me ; The converting power of grace -- I once was lost but now am found ; The clear perspective of grace -- Was blind, but now I see ; The comforting provision of grace -- 'Twas grace that taught my heart to fear and grace my fears relieved ; The connecting point of grace -- How precious did that grace appear the hour I first believed -- Part Two: Grace for the present : The confusing paradox of grace -- Through many dangers, toils, and snares I have already come ; The confident promise of grace -- 'Tis grace hath brought me safe thus far, and grace will lead me home -- Part Three: Grace for the future : The compelling prospect of grace -- When we've been there ten thousand years, bright shining as the sun ; The continual praise of grace -- We've no less days to sing God's praise than when we first begun -- Finale: Captured forever.
"'Amazing Grace' lyrics by John Newton, words from the apostle Paul ... both men ..."
Includes bibliographical references (pages 209-216).
Keywords: Newton, John, -- 1725-1807.; Paul, -- the Apostle, Saint; Amazing grace (Hymn); Grace (Theology); Nonfiction